Continental Monophyly and Molecular Divergence of Peninsular Malaysia's Macaca fascicularis fascicularis - Abdul-Latiff, Muhammad Abu Bakar (Hindawi Publishing Corporation, 2014)

(untitled)
The phylogenetic relationships of long-tailed macaque (Macaca fascicularis fascicularis) populations distributed in Peninsular Malaysia in relation to other regions remain unknown. The aim of this study was to reveal the phylogeography and population genetics of Peninsular Malaysia's M. f. fascicularis based on the D-loop region of mitochondrial DNA. Sixty-five haplotypes were detected in all populations, with only Vietnam and Cambodia sharing four haplotypes. The minimum-spanning network projected a distant relationship between Peninsular Malaysian and insular populations. Genetic differentiation (F (ST), Nst) results suggested that the gene flow among Peninsular Malaysian and the other populations is very low. Phylogenetic tree reconstructions indicated a monophyletic clade of Malaysia's population with continental populations (NJ = 97%, MP = 76%, and Bayesian = 1.00 posterior probabilities). The results demonstrate that Peninsular Malaysia's M. f. fascicularis belonged to Indochinese populations as opposed to the previously claimed Sundaic populations. M. f. fascicularis groups are estimated to have colonized Peninsular Malaysia ~0.47 million years ago (MYA) directly from Indochina through seaways, by means of natural sea rafting, or through terrestrial radiation during continental shelf emersion. Here, the Isthmus of Kra played a central part as biogeographical barriers that then separated it from the remaining continental populations.